Analisis Manajemen Risiko terhadap Jasa Pengiriman Barang JNE Cabang Tasikmalaya - Gina Cissy Aprilia; Muhammad Ukasyah; Naufal Dzakwan Ramadhan; Try Nurhayati Iswanto; Tiara Putri; Syti Sarah Maesaroh (STIE Wiyatamandala, 2023)
The shopping style of people who are shifting from conventional to online has had a major impact on the freight forwarding service industry. Shipping companies cannot be separated from various risks that occur, such as human resources, systems, and internal and external risks. This study aims to determine the most dominant variable and can be a risk for the JNE freight forwarder company. The method used is the descriptive qualitative method. Data collection techniques were used, namely observation, interviews, and literature study. This case study focuses on the JNE Tasikmalaya expedition which took place on Juanda City of Tasikmalaya. After conducting interviews, it can be found that one of the causes of risks to freight forwarding services is centered on the potential of available human resources. Based on the results of research that has been done, it can be seen that human resources and security have the greatest impact on preventing risk management and can increase customer satisfaction, whereas good human resources have a positive and significant impact.